2022
DOI: 10.3390/su14031145
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Soil and Sand from Playgrounds of Çanakkale City (Turkey), and Related Health Risks for Children

Abstract: Children spend most of their time in playgrounds and, in parallel, constitute the social group most sensitive to contaminants. Here, we present the results of a comparative study of heavy-metal contents between soils and sand from sandboxes obtained from playgrounds of Çanakkale city. Average contents of soils followed the order of iron (Fe) (12,901 mg kg−1) > manganese (Mn) (475 mg kg−1) > zinc (Zn) (58 mg kg−1) > copper (Cu) (28 mg kg−1) > nickel (Ni), chromium (Cr) (21 mg kg−1) > lead (Pb) (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Dust can also accelerate environmental pollution by suspending and transporting particulate-bound PTEs; hence, it is considered a key pertinent indicator of urban environmental quality and human health [8,9]. PTEs have frequently been investigated in the soil and street dust of numerous cities around the globe [10][11][12][13][14]. The focus, however, has mainly been on typical urban elements, such as Pb, Cd, Cu, and Zn [15][16][17], while mercury (Hg) as a hazardous contaminant has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Dust can also accelerate environmental pollution by suspending and transporting particulate-bound PTEs; hence, it is considered a key pertinent indicator of urban environmental quality and human health [8,9]. PTEs have frequently been investigated in the soil and street dust of numerous cities around the globe [10][11][12][13][14]. The focus, however, has mainly been on typical urban elements, such as Pb, Cd, Cu, and Zn [15][16][17], while mercury (Hg) as a hazardous contaminant has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…The Pb levels were similar to the ranges measured in coastal municipalities of Montenegro, but the mean of the six sites was higher than the mean reported in Çanakkale (Turkey) and Uppsala (Sweden) (Table 5). [73] Note: Atomic Absorption Spectroscopy (AAS), Graphite Furnace (GF-), Dynamic Reaction Cell (-DRC), Inductively Coupled Plasma Mass Spectrometry (ICP-MS), Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES), Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-OES), Energy Dispersive X-ray Fluorescence (EDXR), X-ray Fluorescence (XRF).…”
Section: Discussionmentioning
confidence: 99%
“…A range of studies have highlighted the significant health risks posed by heavy metal contamination in different ecosystems [ 17 , [22] , [23] , [24] , [25] ]. In the Pearl River Delta urban agglomeration of China, Zheng et al [ 26 ] found that cadmium was the most common pollutant, with the highest risks associated with rice and maize consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In China, Yang et al [ 29 ], reported health risks from heavy metal exposure in farmland, with arsenic, chromium, and cadmium posing the greatest concerns. X. Liu et al [ 30 ], found significant heavy metal contamination in soils, with chromium and lead posing the primary non-cancer risks and cadmium the greatest cancer risk while the heavy metal contents (Cr, Pb, Zn, Cu, Ni) in soils and sand from playgrounds in Çanakkale, Turkey were below international limits, indicating no immediate need for remediation [ 24 ]. While numerous studies have addressed heavy metal contamination in various ecosystems, none have specifically focused on human health risk assessment associated with potentially toxic elements in altered peatlands, despite their recognized role as heavy metal sinks.…”
Section: Introductionmentioning
confidence: 99%